The Role of By-Products of Fruit and Vegetable Processing for the Dietary Treatment of Cardiovascular Risk Factors: A Narrative Review - Isabela Ribeiro Grangeira Tavares; Vivian dos Santos Pinheiro; Patrícia Marques Lisboa Aroso de Castro; Isabelle Barbosa Reis; Gustavo Vieira de Oliveira; Thiago Silveira Alvares (MDPI AG, 2022)
Polyphenols-rich food has been utilized to induce a positive effect on human health. Considering that fruit and vegetable by-products (seeds, pomace, and peels) are sources of polyphenols, previous studies have investigated the effect of dietary supplementation with food by-products on cardiometabolic disorders, such as high fasting blood glucose, dyslipidemia, and obesity. Endothelial dysfunction has also been considered a cardiometabolic parameter, given that it precedes cardiovascular disease. However, there is a scarcity of narrative reviews reporting the effect of food by-product supplementation on cardiometabolic disorders in animal and human clinical trials. In this sense, the present narrative review aims to investigate the impact of fruit and vegetable by-product supplementation on cardiometabolic disorders in humans and animals, exploring the possible mechanisms whenever possible. Research articles were retrieved based on a search of the following databases: PubMed, ScienceDirect, and Google Scholar using the following keywords and synonyms combined: ("fruit by-products" or "food waste" or "pomace" or "bagasse" or "seeds" or "waste products") AND ("heart disease risk factors" or "endothelial dysfunction" or "atherosclerosis"). It was shown that fruit and vegetable by-products could efficiently improve cardiometabolic disorders in patients with chronic diseases, including hypertension, type II diabetes mellitus, and dyslipidemia. Such effects can be induced by the polyphenols present in food by-products. In conclusion, food by-product supplementation has a positive effect on cardiometabolic disorders. However, further studies investigating the effect of food by-products on cardiometabolic disorders in humans are still necessary so that solid conclusions can be drawn.